Survei pangan nabati berpotensi sebagai galaktogogum - Alin Liana (Jurusan Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2021)
Breast milk is an ideal food for babies because of its unique nutritional content. So, every baby should be sought to get exclusive breastfeeding until the age of 6 months. To achieve this, the baby's mother must try to increase the volume and quality of her milk. These efforts must be supported by providing appropriate nutritional intake for breastfeeding mothers. This study is a survey study to determine the type of food consumed by mothers as galactogogums. Questionnaires were distributed openly to breastfeeding mothers and the breastfeeding community. There are 50 respondents who are breastfeeding mothers who have filled out the survey. Respondents came from 17 cities in Indonesia. The data obtained were analyzed descriptively to reveal the types of food used as galactogogums by breastfeeding mothers in Indonesia. The survey results show that there are 15 plant foods consumed by breastfeeding mothers as galactogogums. The dominant vegetable foods consumed are katuk leaves, nuts, moringa leaves, spinach leaves, and banana blossoms. Other types of food, although they are not widely consumed by the community as galactogogums, these foods should still receive the attention of researchers for further study.